A review of selected small scale seawater intakes in South Africa and an investigation into abstraction from the surfzone on rocky coastlines, by means of the horizontal well method - Brahmin, Arivindra (Stellenbosch : Stellenbosch University, 2011)
Thesis (MScEng)--Stellenbosch University, 2011.